2016
DOI: 10.1515/bejeap-2015-0167
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Control and Crime: Medicinal Use, Depenalization and the War on Drugs

Abstract: To date, 27 states and the District of Columbia have passed laws easing marijuana control. This paper examines the relationship between the legalization of medical marijuana, depenalization of possession, and the incidence of non-drug crime. Using state panel data from 1970 to 2012, results show evidence of 4–12 % reductions in robberies, larcenies, and burglaries due to the legalization of medical marijuana, but that depenalization has little effect and may instead increase crime rates. These effects are supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Several studies explored the impact of state medical cannabis legalisation on violent and property crime [24][25][26][27] with one noting significant reductions [25]. Other studies report reductions in subsets of the data; for example, Chu and Townsend [27] noted that California experienced a significant reduction (by 20%), Morris et al [26] observed a slight but significant reduction in state homicides, and Gavrilova et al [24] detected significantly reduced crime in states bordering Mexico.…”
Section: Public Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies explored the impact of state medical cannabis legalisation on violent and property crime [24][25][26][27] with one noting significant reductions [25]. Other studies report reductions in subsets of the data; for example, Chu and Townsend [27] noted that California experienced a significant reduction (by 20%), Morris et al [26] observed a slight but significant reduction in state homicides, and Gavrilova et al [24] detected significantly reduced crime in states bordering Mexico.…”
Section: Public Safetymentioning
confidence: 99%
“…Mixed findings for retail sales sites, with some evidence of a reduction in violent crime [29] and other evidence of no significant impact [30] in Denver, Colorado. Medical cannabis legalisation: State medical cannabis laws associated with significant reductions [25] or no change [24,26,27]. Evidence of reductions in states bordering Mexico [24,27], and some evidence of reduction in homicide rate [26].…”
Section: Number and Incidence Of All-cause Motor Vehicle Crash Injurimentioning
confidence: 99%
“…By transitioning marijuana transactions from illegitimate exchanges that had to be actively enforced to legitimate transactions, there is an immediate reduction in the burden of enforcement assuming the legal market replaces the black market (Miron & Zwiebel, 1995;Edward M Shepard & Blackley, 2005). Law enforcement and the Courts may then transition resources to other, arguably more violent, types of crimes (Huber, Newman, & LaFave, 2016;Miron & Zwiebel, 1995). Second, there is the potential for liberalization laws to influence crime rates through an increase in marijuana (mis)use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The enactment of state laws since 1996 provide an opportunity to empirically test the effect of regulated markets on outcomes of interest. Studies have evaluated outcomes such as marijuana use (Chu, 2014;Harper, Strumpf, & Kaufman, 2012;Deborah S. Hasin et al, 2015;Lynne-Landsman, Livingston, & Wagenaar, 2013;Pacula, Powell, Heaton, & Sevigny, 2015;Wall et al, 2011;Wen, Hockenberry, & Cummings, 2015), crime rates (Chu & Townsend, 2017;Gavrilova, Kamada, & Zoutman, 2017;Huber et al, 2016;Morris, TenEyck, Barnes, & Kovandzic, 2014;Edward M. Shepard & Blackley, 2016), and other health outcomes (D. M. Anderson, Rees, & Sabia, 2014;Chu, 2015;Smart, 2015). These studies all use a difference-in-difference methodology where the treatment is a change in a state law that loosens restrictions on the sale of marijuana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation